Prevention Of Lack of Nutrition And Stunting through Class of Pregnant Women And Toddlers 0 – 5 Years: Pencegahan Gizi Kurang Dan Stunting Melalui Kelas Ibu Hamil Dan Balita 0 – 5 Tahun - Leni Tri Wahyuni; Helda; Aida Yulia; Nur Afriyanti (KPN Kopertis X, 2022)
Nutritional status is an indicator of success in health development in Indonesia. One of the nutritional problems that is still a serious challenge for health workers is malnutrition in toddlers and toddlers. Even though toddlers are the seeds of the nation's future generation. Toddlers themselves are very vulnerable to experiencing health problems as a result of poor nutritional status. Given that toddler age is the beginning of child growth and development. The impact of malnutrition on toddlers is quite diverse, including increasing the risk of infectious diseases, inhibiting the growth and development of children, causing health problems during adolescence and adulthood, and even increasing the risk of child death. This community service activity aims to increase knowledge and develop the skills of pregnant women and toddlers in meeting nutritional needs during pregnancy and toddler nutrition as well as managing healthy eating for toddlers. The methods used in the activity is counseling/education, demonstrations, and competitions for healthy infants and toddlers. The results of this activity helped almost all participants to understand infant nutrition and pregnant women's nutrition and participants were also able to manage food accordingly